Aortic remodelling after thoracic endovascular aortic repair in acute and chronic type B aortic dissections. (23rd June 2020) - Dohle, Daniel-Sebastian; Laverne, Travis; Bavaria, Joseph; Savino, Danielle; Vallabhajosyula, Prashant; Szeto, Wilson Y; Siki, Mary; Wang, Grace; Jackson, Benjamin; Desai, Nimesh
Abstract: OBJECTIVES: Type B aortic dissections are routinely treated with thoracic endovascular aortic repair (TEVAR). The timing for TEVAR remains controversial and might have an impact on the remodelling capacity of the aorta. This study analyses and compares aortic remodelling in acute (ABD) and chronic (CBD) type B aortic dissections after TEVAR. METHODS: This retrospective study analysed the preoperative, postoperative and at least 1-year follow-up computed tomography of 53 TEVAR patients (36 ABD, 17 CBD) at a single institution between May 2005 and May 2016. The volumes of aortic lumen (AL), true lumen, false lumen (FL) and perfused FL were measured at the stent graft level (A), from the stent graft to the coeliac trunk (B) and from the coeliac trunk to the bifurcation (C). The absolute volumes, normalized volume changes and FL thrombosis rate of ABD and CBD patients were compared. RESULTS: Absolute AL and FL of segment A were significantly larger in CBD patients compared to ABD patients preoperatively (AL: 354 ± 68 vs 255 ± 51 ml, P = 0.023, FL: 253 ± 56 vs 183 ± 35 ml, P = 0.028) until last follow-up (AL: 462 ± 52 vs 246 ± 52 ml, P = 0.003, FL: 268 ± 202 vs 91 ± 31 ml, P = 0.004). The true lumen in segment A increased more in ABD than in CBD patients preoperatively to postoperatively (112% vs 36% P < 0.001) and within the first year postoperatively (171% vs 80% P < 0.001). FL in segment A decreased more in ABD compared to CBD patients within the first year (−42% vs −13% P < 0.001) and thereafter (−50% vs +6% P = 0.002). In segments B and C, the FL thrombosis rate was higher in ABD than in CBD patients at all time points and significantly higher in segment A after the first year (91% vs 98% P = 0.035). CONCLUSIONS: Aortic remodelling after TEVAR is significantly different in acute and chronic dissection patients. TEVAR promotes aortic remodelling in both acute and chronic dissections in terms of true lumen increase at stent graft level. Nevertheless, significant AL reduction by FL shrinkage is primarily found in ABD.